2016
DOI: 10.21082/p.v14n2.2015.113-124
|View full text |Cite
|
Sign up to set email alerts
|

Strategi Peningkatan Produktivitas Lada dengan Tajar Tinggi dan Pemangkasan Intensif serta Kemungkinan Adopsinya di Indonesia

Abstract: <p>RINGKASAN<br /><br />Lada merupakan salah satu komoditas ekspor tradisional penting Indonesia. Capaian produktivitasnya secara nasional masih rendah (&lt; 1.0 ton/ha), di bawah produktivitas negara penghasil utama lada lain seperti Vietnam, Brazil dan Malaysia. Banyak faktor yang diperkirakan berkontribusi terhadap rendahnya produktivitas. Faktor tersebut dapat berupa kendala teknis maupun non teknis. Di antara sejumlah kendala teknis, aspek agronomi seperti kebiasaan petani menggunaka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 1 publication
0
7
0
4
Order By: Relevance
“…It was suggested that living standard should have the following characteristics: a) Longevity, b) Allows pepper roots to attach firmly, c) Has no negative effects on pepper plants, such as competition for nutrients, water, and CO2, allelopathic effect, d) Easy and fast to grow and resistant to pruning, e) Economical and easy to obtain. Also, the stem diameter should not be too large, relatively resistant to pests and diseases [8], not a host for pests and diseases of pepper, from the Leguminosae family, and have deep roots. The living standards provide shade so that the microclimatic conditions below are affected, which results in all agronomic aspects of the plants underneath.…”
Section: Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that living standard should have the following characteristics: a) Longevity, b) Allows pepper roots to attach firmly, c) Has no negative effects on pepper plants, such as competition for nutrients, water, and CO2, allelopathic effect, d) Easy and fast to grow and resistant to pruning, e) Economical and easy to obtain. Also, the stem diameter should not be too large, relatively resistant to pests and diseases [8], not a host for pests and diseases of pepper, from the Leguminosae family, and have deep roots. The living standards provide shade so that the microclimatic conditions below are affected, which results in all agronomic aspects of the plants underneath.…”
Section: Growthmentioning
confidence: 99%
“…Pepper plants can grow at a temperature of 10-40 o C, and the ideal temperature is 23-32 o C [8], but due to the hot temperature throughout the third year > 30˚C in Muktiharjo, the sunlight penetrated more than 70 %, so the plants became dry and could not bear fruit. Nutrients can increase plant resistance to environmental stresses.…”
Section: Growthmentioning
confidence: 99%
“…Indonesian Spices and Medicinal Crops Research Institute (ISMCRI) has released high-yielding pepper varieties with 2 -4.8 tons productivity.ha-1 (Wahyudi & Pribadi 2016). The use of live supports with more than 5.0 rm in height, followed by intensified pruning of black pepper vines and their live supports increased the productivity of black pepper higher than 1.5 tons.ha-1 per year (Daras 2016). Tjahjana et al (2012) reported that pepper productivity in Lampung yielded 1.6 tons.ha-1 from 7 years old plants fertilized with 1.6 kg NPKMg (12:12:17:2) per tree.…”
Section: The Unit Cost Of Production and Relative Competitivenessmentioning
confidence: 99%
“…Secara tradisional produksi lada di Kalimantan Timur menggunakan tiang panjat mati dengan jarak tanam bervariasi antara 1.5m x 1.5m sampai 2.0m x 1.8m dengan populasi antara 2700 tanaman hingga 4200 tanaman tiap ha. Penggunaan tajar hidup berukuran tinggi (> 5 m) yang dipangkas 3 kali setahun, dan pemangkasan tanaman pokok lada 3-4 kali hingga mencapai tinggi tajar yang diinginkan (5-6 m) disertai pemupukan berimbang dan penggunaan bibit unggul, berpotensi meningkatkan produksi dan produktivitas lada nasional secara signifikan (Daras 2015).…”
Section: Inovasi Teknologi Mendorong Keberlanjutanunclassified